Pengembangan Media Science Crossword Game Berbantuan Canva untuk Meningkatkan Kemampuan Berpikir Kritis dan Kreativitas Siswa Kelas 5 SD - Himah, Musabiku Choiriyatul; Oktaviani, Ragil Tri; Amalia, Shofi Nur (Literasi: Jurnal Ilmu Pendidikan, 2024)
This research aims to develop Science Crossword Game media assisted by Canva to improve the critical thinking and creativity skills of 5th grade students at Zaid Bin Tsabit Creative SDI, Bitar Regency. This research method is research and development Research and Development (R&D). The subject of this research is class 5. The research location is SDI Creative Zaid Bin Thabit, Bitar Regency. Data collection uses observation, interviews, tests, questionnaires, documentation. The data analysis techniques used are the gutmaan scale, Likert scale, and gain score formula. The results of the research show that the development of the Science Crossword Game media assisted by Canva to improve the critical thinking skills and creativity of grade 5 students is as follows: a) The validity and feasibility of the Science Crossword Game media assisted by Canva, the results of material expert validation obtained an overall average of 3.5 with a percentage of 87% is in the "Very Valid" category, while media expert validation gets an overall average of 3.6 with a percentage of 90% in the "Very Valid" category and media feasibility gets an overall average of 3.9 with a percentage of 98% in the "Very Valid" category. Feasible", b) The form of developing science crossword game media on the human digestive system material can improve critical thinking skills obtained from the pre-test and post-test getting an average of 0.72 in the "high" category, c) The form of developing science crossword game media on digestive system material Humans can increase students' creativity from the results of questionnaires before and after using media. The results before using the media were 63% in the "fairly good" category, while after using the media they were 93% in the "very good" category. So the development of Science Crossword Game media with the help of Canva can improve the critical thinking skills and creativity of fifth grade students. Keywords: science crossword game, critical thinking skills, creativity